(3GbJUGOjGJ GdJLGQI GdOhdjI (B/s - (3RGjQj, HdbGSes ((3GdLRGFQ(B: s (3OGQ GdCjGe ddfTQ hGdJhRjY(B, s, 2013)
(3eONd YGe dOQGSI GbJUGOjGJ GdJLGQI GdOhdjI, JMdjd fXQjI GdJLGQI GdOhdjI YfO GdcdGSjc hGdJYOjdGJ GdJj CONdJ Ydi GdfehOL GdCSGSj, JWhjQ fXQjI QjcGQOh aj GdJLGQI GdOhdjI, efMfi GdWdH GdeJHGOd h fXQjI GdJLGQI GdOhdjI, fehOL fSH YfGUQ GdEfJGL dgjcTQCDdjf, JMOjK fXQjGJ GdJLGQI GdOhdjI(B.s
(3GdeQGLY U(B.377s
Keywords: (3GdJHGOd GdJLGQjs; (3GdJLGQI GdNGQLjIs; (3GdJLGQI GdOhdjIs